Non-Motor Symptoms of Parkinson’s Disease and Their Impact on Quality of Life in a Cohort of Moroccan Patients - Tibar, Houyam; El Bayad, Khalil; Bouhouche, Ahmed; Ait Ben Haddou, El Hachmia; Benomar, Ali; Yahyaoui, Mohamed; Benazzouz, Abdelhamid; Regragui, Wafa (Frontiers in Neurology, 2018)
Background: Non-motor symptoms (NMSs) are a real burden in Parkinson's disease (PD). They may appear in early pre-symptomatic stage as well as throughout the disease course. However, their relationship with the deterioration of the patient's quality of life (QoL) is still under debate. The present study aimed to investigate the prevalence of NMSs and their impact on the QoL in a cohort of Moroccan patients. Methods: We carried out a cross-transactional study where a total of 117 patients were submitted to a structured clinical interview and examination investigating motor and NMSs based on common and conventional scales. Motor symptoms were assessed by the UPDRS I to VI during ON condition. The NMSs were evaluated with common scales and their relationship with the QoL was investigated. Results: The mean patient's age was 60.77±11.36 years-old, and the median disease duration was 6 years [2.5-9.5]. Motor's phenotype subtypes were the mixed form in 40.2% of patients, akinetic-rigid in 20.5% and a tremor-dominant form in 39.3%. The median Hoehn and Yahr staging was 2 [1-2.5]. Regarding NMSs, the most common were urinary dysfunctions (82.6%), sleep (80.6%) and gastrointestinal (80%) disorders. Other autonomic dysfunctions were also frequent: thermoregulatory dysfunctions 58.6%, cardiovascular troubles 50.9% and sexual dysfunctions 47.9%. Depression was present in 47.9% and fatigue symptoms in 23.1%. The median score of SCOPA-AUT was 14 [7.75-21.80]. The median PD questionnaire 39-Score index (PDQ39-SI) was 23.22% and the most affected dimension was "mobility". Univariate and multivariate analyses showed that the SCOPA-AUT score impacted the QoL (p=0.001), especially the gastrointestinal (p=0.007), and cardiovascular (p=0.049) dimensions. Conclusion: Our data show that all patients have presented at least one NMS. Autonomic and sleep disorders were the most frequent, and in contrast to other studies, digestive and cardiovascular disorders were rather the factors influencing negatively the QoL of patients. Understanding the pathophysiology of these NMSs should be placed at the forefront in order to develop new therapeutic approaches improving the QoL of PD patients.